2021
DOI: 10.1590/1984-70332021v21n3a40
|View full text |Cite
|
Sign up to set email alerts
|

Callus induction and pro-embryogenic mass formation in Myrciaria dubia, an important medicinal and nutritional plant

Abstract: Caçari is a fruit tree that is native to the Amazon region of Brazil. The fruit is considered to have the highest vitamin C content of any edible fruit (13.757 mg 100 g -1 dry weight). The objective of this study was to evaluate the effects of 2,4-D and 6-BAP alone or in combination on in vitro callus induction and pro-embryogenic mass formation in caçari stem segments in different culture media as a precursor for caçari micropropagation. The experiment consisted of two culture media (MS and WPM) and combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several factors influence somatic embryogenesis induction, such as genotype (Dias et al 2018) and the source of explants (Ara ujo et al 2021). In our study, somatic embryo induction was observed only in PEMs induced from stem nodal segments, which were more responsive to all plant growth regulators in greater concentrations (range, 4-6 mgÁL -1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors influence somatic embryogenesis induction, such as genotype (Dias et al 2018) and the source of explants (Ara ujo et al 2021). In our study, somatic embryo induction was observed only in PEMs induced from stem nodal segments, which were more responsive to all plant growth regulators in greater concentrations (range, 4-6 mgÁL -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic embryogenesis is a widely used technique for large-scale in vitro propagation of many species (Von Arnold et al 2002). The process of somatic embryo induction and plant regeneration is influenced by several factors, such as species, explant source, culture medium, and type and concentration of auxins and cytokinins (Araujo et al 2016;Ara ujo et al 2021;Gulzar et al 2020;W ojcikowska and Gaj 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation